2012
DOI: 10.1016/j.bpj.2012.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Quantification of Biomolecular Interactions by Fluorescence Cross-Correlation Spectroscopy

Abstract: Fluorescence cross-correlation spectroscopy (FCCS) is used to determine interactions and dissociation constants (K(d)s) of biomolecules. The determination of a K(d) depends on the accurate measurement of the auto- and cross-correlation function (ACF and CCF) amplitudes. In the case of complete binding, the ratio of the CCF/ACF amplitudes is expected to be 1. However, measurements performed on tandem fluorescent proteins (FPs), in which two different FPs are linked, yield CCF/ACF amplitude ratios of ~0.5 or les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
136
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(152 citation statements)
references
References 47 publications
13
136
3
Order By: Relevance
“…As reported previously, mEGFP exhibited sufficiently bright fluorescence, a small triplet fraction, and resistance to photobleaching. In contrast, substantial triplet fractions were detected in tdTomato and mCherry, as reported previously (38). Furthermore, Foo et al reported previously that the low maturation efficiency of mCherry affected FCCS analysis (38).…”
Section: Methodssupporting
confidence: 82%
“…As reported previously, mEGFP exhibited sufficiently bright fluorescence, a small triplet fraction, and resistance to photobleaching. In contrast, substantial triplet fractions were detected in tdTomato and mCherry, as reported previously (38). Furthermore, Foo et al reported previously that the low maturation efficiency of mCherry affected FCCS analysis (38).…”
Section: Methodssupporting
confidence: 82%
“…1 A); the value is the average from measurements on both membranes and at both temperatures, errors are given as the SE of the mean (mean 5 SE) unless stated otherwise. The apparent complex fraction <100% can be explained by incomplete maturation of mRFP and its prolonged residence in dark or dim states, as discussed in detail earlier (57,58). The apparent complex fraction of mRFP-EGFR-eGFP in COS-7 and HEK293 cells was 68 5 2% and 58 5 1%, respectively.…”
Section: Egfr Complex Fractions and Receptor Density Determined By Swmentioning
confidence: 81%
“…Only cells with expression levels of the two fluorescent proteins differing by a factor of <2 were selected for data processing and evaluation (57). Positive and negative controls were performed for each cell line and each temperature to determine the dynamic range of our method.…”
Section: Egfr Complex Fractions and Receptor Density Determined By Swmentioning
confidence: 99%
“…Quantitative analysis of protein-protein interactions in living cells has been performed by single-wavelength fluorescence cross-correlation spectroscopy [12,13,16], although twolaser-beam FCCS was also used to quantify biological interactions [15,[17][18][19]. In this work, we used two-laser-beam FCCS instead of single-beam FCCS because the two-laser FCCS has more flexible laser power tuning for each fluorescence probe, providing accurate measurement of fluorescence intensity.…”
Section: Discussionmentioning
confidence: 99%
“…The femtoliter confocal volume is well suited to resolve the different measurement positions even in live cells. FCCS has various applications to determine quantitative parameters, including determination of the dissociation constant in the living cell [12][13][14][15][16][17][18][19]. Indeed, single wavelength fluorescence cross-correlation spectroscopy has been employed for determination of dissociation constants [12,13,16].…”
Section: Introductionmentioning
confidence: 99%